Introduction to electric power engineering - Shultz, Richard D.; Smith, Richard A. ([S.l.] : Longman Higher Education, 1985)
Presents the fundamentals of the electric power industry at an early level--the prerequisite is a course in introductory circuits. Integrated approach treats electric machinery as a part of the total power system, avoiding the common separation of the machinery from power system analysis. Covers the principles of electric power engineering, tracing the generation and application of electric power from the synchronous generator out through the step-up transformer, the transmission system, and the loads. Chapters are self-contained, making this text very flexible.